Student Literacy Through Library Visits and Gemini AI Programs at SD Negeri Potrobangsan 2 - Yarmini, Yarmini; Supriadi, Didi; Purnami, Sri (Malikussaleh University, Aceh, Indonesia, 2025)
People often say that literacy is the foundation for a person's lifelong education. Improving students' literacy skills is one of the main focuses in today's education world. Literacy, which includes reading, writing, and understanding information well, is an essential foundation in the learning process at all levels of education. Good literacy skills help students succeed academically and equip them with the critical and analytical thinking skills needed in everyday life. We need to consider literacy development because it is a fundamental ability that every individual must possess to navigate life in the future. This study aims to develop a strategy to improve the literacy of fifth-grade students at SD Negeri Potrobangsan 2 through a combination of library visits and the Gemini AI program. We expect library visits to cultivate students' interest in reading physical books, while the Gemini AI program serves as an interactive digital literacy medium to enhance students' learning experiences. This research approach uses a qualitative method with observation, in-depth interviews, and focus group discussions (FGD) as the primary instruments for data collection. The study results indicate that integrating traditional literacy learning with digital technology can improve students' literacy skills holistically. Students showed increased reading comprehension, higher involvement in literacy activities, and mastery of digital literacy skills. Implementing this strategy also increased motivation among students to read and utilize the library optimally. Therefore, elementary schools can apply this strategy as an effective literacy learning model.